2018
DOI: 10.3847/1538-4357/aab03d
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Proton Cyclotron Resonance as a Dissipation Mechanism in Solar Wind Turbulence: A Statistical Study at Ion-kinetic Scales

Abstract: We use magnetic field and ion moment data from the MFI and SWE instruments onboard the Wind spacecraft to study the nature of solar wind turbulence at ion-kinetic scales. We analyze the spectral properties of magnetic field fluctuations between 0.1 and 5.5 Hz over 2012 using an automated routine, computing high-resolution 92 s power and magnetic helicity spectra. To ensure the spectral features are physical, we make the first in-flight measurement of the MFI 'noise-floor' using tail-lobe crossings of the Earth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
85
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(101 citation statements)
references
References 134 publications
9
85
0
Order By: Relevance
“…Gary (1986). The results here also complement the studies of the magnetic helicity (He et al, 2011;Podesta and Gary, 2011;Klein et al, 2014b;Bruno and Telloni, 2015;Woodham et al, 2018), which have shown a signature consistent with ICWs for intervals of fast solar wind. Bruno and Telloni (2015) also demonstrated the reduction and disappearance of this component as the velocity transitioned from fast to slow.…”
Section: Anisotropysupporting
confidence: 84%
See 1 more Smart Citation
“…Gary (1986). The results here also complement the studies of the magnetic helicity (He et al, 2011;Podesta and Gary, 2011;Klein et al, 2014b;Bruno and Telloni, 2015;Woodham et al, 2018), which have shown a signature consistent with ICWs for intervals of fast solar wind. Bruno and Telloni (2015) also demonstrated the reduction and disappearance of this component as the velocity transitioned from fast to slow.…”
Section: Anisotropysupporting
confidence: 84%
“…Although the plasma β values are much less extreme than the cases reported in Chen et al (2014), we demonstrate that such a study is currently possible in the wave-vector domain with multi-point measurements. However, the break in the parallel component is closer to the combined inertial and gyro scales suggesting that cyclotron damping may be important (Roberts and Li, 2015;Woodham et al, 2018).…”
Section: One-dimensional Spectramentioning
confidence: 99%
“…The ratio f b /f c approaches unity near the Sun, which may be due to the increased activity of the solar wind plasma close to the Sun generating ion cyclotron waves (Bowen 2020, submitted, this volume). Regarding that f b /f c deviates slightly from unity (less than unity) in the slow solar wind at 1 AU (Woodham et al 2018) and that f b /f c increases slightly with decreasing heliocentric distance in the slow solar wind, it seems to be a natural result for f b /f c to approach unity near the Sun.…”
Section: Resultsmentioning
confidence: 94%
“…where Ω p = qB 0 /m p the ± relates to the direction of the wave propagation relative to the particles motion (Woodham et al 2018).…”
Section: Wave Frequencies and Ion Scalesmentioning
confidence: 99%
“…In the solar wind, observations of non-zero magnetic helicity at ion scales have been interpreted as evidence for active cyclotron damping of turbulent fluctuations which contribute to the dissipation and heating at kinetic scales (Isenberg 1990;Leamon et al 1998;Woodham et al 2018). In addition to proton-cyclotron dynamics, the cyclotron resonance of doubly ionized helium (α-particles) and heavy ions has been studied extensively (Isenberg, & Hollweg 1983;Isenberg 1984).…”
Section: Introductionmentioning
confidence: 99%